INNOVATIVE TECHNOLOGIES AND ADVANCED FOREIGN EXPERIENCE IN TEACHING THE RUSSIAN LANGUAGE - Diyorova Nargiza Omonovna (Bright Mind Publishing, 2025)
This article analyzes the importance of innovative technologies in teaching the Russian language, their level of effectiveness and integration into the educational process. It also highlights the experience of foreign countries, especially interactive methods based on digital technologies, their role in increasing motivation in language learning. The article shows modern pedagogical approaches and mechanisms for their application in practice through examples.
Keywords: Innovative technologies, Russian language, foreign experience, interactive methods, digital education, modern lesson, language learning, motivation, online platforms.